PENGARUH TATA RUANG KANTOR TERHADAP KINERJA KARYAWAN PADA PT. SUCOFINDO (PERSERO) MEDAN - Iswandi Idris; Palti Raja Halomoan (JURNAL LENTERA BISNIS, 2020)
Office Spatial Planning arrangement of office space and office preparation equipment and furniture on the floor area and office space available to offer facilities for workers. PT. Sucofindo (Persero) Medan Branch is a company engaged in consulting services, testing, providing training and providing certification services such as, ISO 9001: 2008 Certification. Type of quantitative research, with the type of data obtained from primary and secondary data, and research methods of data collection using interviews, observation, and questionnaires. Based on the research results of the relationship (correlation) the strongest indicator is Xi with Yi, namely R = 0.745 and the contribution contributed by 55.50%. The regression test results show that the most dominant indicator of the regression equation, Xi to Yi, is 0.962. And the t-test results show that the most dominant indicator is Xi against Yi, that is t count = 3.406 where t table 2.16 then t count 3.406> t table 2.16 or in other words (Ha) accepted, meaning that there is a significant influence between Xi and Yi. Then the F Test results show that the most dominant indicator is Xi against Yi, namely F count = 16.196, where F table = 4.67, Ha accepted, meaning that there is a significant influence between Xi to Yi.Key words: Office Spatial Planning, Employee Performance, Multiple Linear Regression Tests